Comprehensive approach to comparative efficiency evaluation of HPS for helicopters. Issue 6 (30th September 2014) - Singh, Riti; Zakharchenko, Victor; Lukovnikov, Alexander
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of the work is to carry out analysis of the possibilities and estimation of electric drive efficiency for rotors of helicopter propulsion systems (PS). Design/methodology/approach – Methodology and comprehensive multidisciplinary technology for efficiency estimation of conventional and unconventional architectures PS on rotorcraft system level at preliminary design phase were developed. Findings – Application of the approach allow to carry out analysis of hybrid (based on gas turbine and piston engines) and full electrical PS for superlight-, light- and medium-size helicopters. Practical implications – It was shown what level of electrical technologies improvement may provide positive effect of the using of hybrid and full electrical helicopter PS of different architectures. Originality/value – Close matching of helicopter and engine design and calculation aspects, as well as possibilities to use the external (experimental) performances of engine components, whole PS and helicopter aerodynamic performance, are the distinctive features of proposed technology and methodology.